The Effectiveness of Commissioners Board Size And Audit Commitee Size on Risk Disclosure - Yubiharto Yubiharto; Walid Rudianti (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study is to analyse the effectiveness of the Commissioners Board size Audit Committee size on risk disclosure (empirical study on coal-mining sub-sector under mining sector companies listed on Indonesian Stock Exchange during the period of 2016-2018). The samples for this study are 19 companies under coal-mining sub-sector listed in Indonesian Stock Exchange during the period of 2016-2018. The methodology used in this study is multiple linear regression with data panel approach. Commissioners Board size has a positive and significant effect on risk disclosure in the companies under mining sector and coal-mining sub sector listed in IDX during the period of 2016-2018. Meanwhile, audit committee size has a negative and significant effect on risk disclosure in the companies under mining sector and coal-mining sub sector listed in IDX during the period of 2016-2018. It is advisable for investors and prospective investors to consider Commissioners Board size and Audit Committee size.